Thiosemicarbazones, semicarbazones, dithiocarbazates and hydrazide/hydrazones: Anti-Mycobacterium tuberculosis activity and cytotoxicity - Pavan, Fernando Rogério [UNESP]; Maia, Pedro I. da S.; Leite, Sergio R. A. [UNESP]; Deflon, Victor M.; Batista, Alzir A.; Sato, Daisy N.; Franzblau, Scott G.; Leite, Clarice Queico Fujimura [UNESP] (Elsevier France-editions Scientifiques Medicales Elsevier, 2010)
The aim of this study was to identify a candidate drug for the development of anti-tuberculosis therapy from previously synthesized compounds based on the thiosemicarbazones, semicarbazones, dithio-carbazates and hydrazide/hydrazones compounds. The minimal inhibitory concentration (MIC) of these compounds against Mycobacterium tuberculosis was determined. Their in vitro cytotoxicity to J774 cells (IC(50)) was determined to establish a selectivity index (SI) (SI = IC(50)/MIC). The best compounds were the thiosemicarbazones (2, 3 and 4) and the hydrazide/hydrazones (14, 15, 16 and 18). The results are comparable to or better than those of "first line" or "second line" drugs commonly used to treat TB, suggesting these compounds as anti-TB drug candidates. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Antimycobacterial agents; REMA; Cytotoxicity; Thiosemicarbazones; Semicarbazones; Dithiocarbazates; Hydrazide/hydrazones